Handbook of marriage and the family / Gary W Peterson, Kevin R Bush - Peterson, Gary W.
Despite waves of societal, cultural, and generational change, the family remains the bedrock unit for studying the individual and society as well as a prime focus of study in its own right. In particular, where diverse family structures were once considered rare occurrences, they are now gaining increased recognition from the social sciences. The Handbook of Marriage and the Family has been updated to reflect the current realities of family life, synthesizing and critiquing the knowledge base in key areas such as dating, parenting, sexuality, gender, ethnicity, sibling relationships, divorce, and stepfamilies. This Third Edition assembles leading experts across the disciplines to cover an expanded range of topics in qualitative and quantitative methodology, roles and relationships, diversity, and application issues, among them: Systemic and ecological qualities of families. Division of household labor. Families with cohabitating parents. Fathers' nurturance of children over the life course. Cultural influences on socialization. Family lives of lesbian and gay adults. Family science as a teaching discipline. Like its predecessors, this new edition of the Handbook of Marriage and the Family stands as a comprehensive primary resource for family scientists, sociologists, psychologists, and social workers who work with families, as well as for researchers, graduate students, and faculty in family studies, child development, psychology, sociology, social work, public health, and related fields.